Theory and technology of rock excavation for civil engineering - Zou, Dingxiang (Springer, 2016)
This book summarizes the technical advances in recent decades and the various theories on rock excavation raised by scholars from different countries, including China and Russia. It not only focuses on rock blasting but also illustrates a number of non-blasting methods, such as mechanical excavation in detail. The book consists of 3 parts: Basic Knowledge, Surface Excavation and Underground Excavation. It presents a variety of technical methods and data from diverse sources in the book, making it a valuable theoretical and practical reference resource for engineers, researchers and postgraduates alike.
2.6.6.2 Button Bits.
Keywords: Rock excavation.; Civil engineering.; elektronické knihy; electronic books